Electro-Fenton treatment of a complex pharmaceutical mixture: Mineralization efficiency and biodegradability enhancement. (August 2020) - Ganzenko, Oleksandra; Trellu, Clément; Oturan, Nihal; Huguenot, David; Péchaud, Yoan; van Hullebusch, Eric D.; Oturan, Mehmet A.
Abstract: Combination of the electro-Fenton process with a post-biological treatment could represent a cost-effective solution for application of electrochemical advanced oxidation processes. The objective of this study was to assess this treatment strategy in the case of a complex pharmaceutical mixture. First, main operating parameters ([Fe 2+ ] and current) of the electro-Fenton process were optimized. An optimal concentration of 0.2 mM of Fe 2+ was obtained for mineralization of the pharmaceutical mixture. An optimal current of 400 mA was also obtained for degradation of caffeine and 5-fluorouracil in the mixture. However, mineralization of the effluent was continuously improved when increasing the current owing to the promotion of mineralization of organic compounds at the BDD anode. Besides, energy efficiency was decreased at prolonged treatment time because of mass transport limitation. Interestingly, it was observed a strong biodegradability enhancement of the solution after short treatment times (<3 h) at 500 and 1000 mA, which can be related to the degradation of parent compounds into more biodegradable by-products. The need for an acclimation time of the biomass to the pre-treated effluent was also emphasized, most probably because of the formation of some toxic by-products as observed during acute toxicity tests. Therefore, a biological post-treatment could represent a cost-effective solution for the removal of biodegradable residual organic compounds as well as for the removal of nitrogen released from mineralization of organic compounds under the form of NO3 − and NH4 + during electro-Fenton pre-treatment. Graphical abstract: Image 1 Highlights: Electro-Fenton (EF) treatment of a mixture of 13 pharmaceuticals. Finding optimal value of 2 main parameters: current and concentration of Fe2+. Nitrogen was released from mineralization of organic compounds as NO3- and NH4+. Strong enhancement of the biodegradability of pharmaceutical mixture by EF treatment.